The Influence of Project Based Learning Model on Elementary School Students' Learning Outcomes and Creativity in Science Learning - Mustika, Wilfa; Oviana, Wati; Nurdin, Syahidan (MANDAILING GLOBAL EDUKASIA, 2025)
Low learning outcomes and student creativity so that in science learning at SD Negeri 2 Gegerung Bener Meriah. This results in a lack of student scores, especially in science lessons. One solution to overcome this problem is to apply a learning model that supports student activity, using the Project Based Learning model in accordance with the syntax of the model. This study aims to determine the effect of the Project Based Learning learning model on student learning outcomes and creativity. This research is a one-group pretest-posttest-design research. The population in this study were all fifth grade students. The sample in this study was selected by Purpose Sampling. The instruments used in this study were Pre-Test and Post- Test test questions for learning outcomes and student creativity observation rubrics. In the data collection technique for student learning outcomes, students are given test questions in the form of initial tests and final tests, then the data is analyzed by the t test. while for data collection of student creativity in the form of an observation rubric filled in by the observer. The results of the statistical test showed that the significance value was 0.04 <0.05, so the Ho hypothesis was accepted, so it could be concluded that there was an effect of the Project Based Learning model on learning outcomes. While for classical student creativity reached 85.71%, it can be said that the level of student creativity in this study is very creative. So it can be concluded that there is an effect of the Project Based Learning model on student creativity compared to learning taught using conventional models.